Characterization of CuO doped CdO nanomaterials synthesized by sol gel spin coating and hydrothermal method - Yildiz, Tulay; Kati, Nida; Gul, Busra (Elsevier, 2023)
CuO-CdO nanomaterials were synthesized by sol gel spin coating and hydrothermal methods. Undoped CdO and 0.2%, 0.5%, 1%, and 2% CuO doped CdO were produced as thin films and nanopowders. The structural, optical, and electrical properties of the thin films and nanopowders produced were investigated. It was determined by X-ray diffraction (XRD) analysis that thin films and nanopowders were polycrystalline and face-centered cubic structures. From Atomic Force Microscope (AFM) images, it was observed that the structure of the thin films was homogeneous and dense rod-shaped structures, and the nanopowders were urchin-like structures consisting of spherical nanoparticles from the Field Emission Scanning Electron Microscopy (FESEM) images. It was determined that nanopowder and thin films have direct band transition from Ultraviolet-visible spectroscopy (UV-Vis) analysis. From all the results obtained, it was concluded that structural, optical, and electrical properties of thin films and nanopowders vary depending on the doping rate and method differences.
Keywords: CdO; CuO; Sol gel; Electrical properties; Hydrothermal